Allosteric Modulation of NMDARs Reverses Patients' Autoantibody Effects in Mice. Issue 1 (January 2022) - Radosevic, Marija; Planagumà, Jesús; Mannara, Francesco; Mellado, Araceli; Aguilar, Esther; Sabater, Lidia; Landa, Jon; García-Serra, Anna; Maudes, Estibaliz; Gasull, Xavier; Lewis, Mike; Dalmau, Josep
Abstract : Background and Objectives: To demonstrate that an analog (SGE-301) of a brain-derived cholesterol metabolite, 24(S)-hydroxycholesterol, which is a selective positive allosteric modulator (PAM) of NMDA receptors (NMDARs), is able to reverse the memory and synaptic alterations caused by CSF from patients with anti-NMDAR encephalitis in an animal model of passive transfer of antibodies. Methods: Four groups of mice received (days 1–14) patients' or controls' CSF via osmotic pumps connected to the cerebroventricular system and from day 11 were treated with daily subcutaneous injections of SGE-301 or vehicle (no drug). Visuospatial memory, locomotor activity (LA), synaptic NMDAR cluster density, hippocampal long-term potentiation (LTP), and paired-pulse facilitation (PPF) were assessed on days 10, 13, 18, and 26 using reported techniques. Results: On day 10, mice infused with patients' CSF, but not controls' CSF, presented a significant visuospatial memory deficit, reduction of NMDAR clusters, and impairment of LTP, whereas LA and PPF were unaffected. These alterations persisted until day 18, the time of maximal deficits in this model. In contrast, mice that received patients' CSF but from day 11 were treated with SGE-301 showed memory recovery (day 13), and on day 18, all paradigms (memory, NMDAR clusters, and LTP) had reversed to values similar to those of controls. On day 26, no differences were observed among experimental groups. Discussion: An oxysterol biology-based PAM of NMDARs is able to reverse the synaptic and memory deficits caused by CSF from patients with anti-NMDAR encephalitis. These findings suggest a novel adjuvant treatment approach that deserves future clinical evaluation.